IS ISLAND TOURISM GOOD FOR ME? SCHOOL-AGED CHILDREN’S VOICES TOWARDS ISLAND TOURISM IMPACTS AND WELL-BEING IN LIFE DOMAINS - Tirasattayapitak, Areeta; Thammajak, Sumattaya (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2019)
This paper reports the perceptions of school-aged children towards island tourism impacts on their sense of well-being in various life domains and level of support for tourism development. Research revealed children’s less than positive perceptions of tourism development, with concerns over negative environmental and socio-cultural impacts of tourism. The children regarded their material well-being without its links to tourism. Moreover, the children noted the high level of negative impacts of tourism in their lives and communities, which seemed to diminish their good sense of safety well-being. Most children showed support for tourism development if it implies their own entrepreneurship. Their major push factor to support tourism was money stimulus that would in turn enhance their healthier quality of life.